Identity at the Border: Narrative Strategies in María Novaro's El jardín del Edén and John Sayles's Lone Star - Amy Kaminsky (Studies in 20th & 21st Century Literature, 2001)
In María Novaro's El jardín del Edén and John Sayles's Lone Star, the narrative and visual art of film functions as ritual does: to make sense of the dangerous liminal space of the border. Novaro and Sayles both locate their protagonists' identity quests in the Mexico-U.S. borderlands, but they approach the problem from different directions: Sayles from the north, Novaro from the south; Sayles from the perspective of men in search of themselves through their fathers, Novaro from that of women in search of identity with the help of each other. With her focus on the stories of three women, and a camera that often interrupts the narrative in favor of the contemplative gaze, Novaro challenges both the conventional plot and the patriarchal substructure that critics have linked to Mexican cinema. When John Sayles investigates identity at the border, he charges headlong into precisely the sort of diachronic narrative that Novaro leaves behind. Yet ironically, it is by embracing narrative that Sayles confounds the boundary lines that the story of paternity is meant to maintain and that U.S. border films have traditionally policed.
Keywords: border narrative; María Novaro; El jardín del Edén; John Sayles; Lone Star; film; space; border; U.S.-Mexico border; identity; patriarchy; Mexican cinema; paternity